Determinants of English Reading Comprehension and Vocabulary Performance among Struggling Grade 7 and Grade 8 Students in Panan-awan Integrated School - Arcelo, Aimee (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the determinants of English reading comprehension and vocabulary performance among struggling Grade 7 and Grade 8 students in Panan-awan Integrated School. Anchored on Self-Determination Theory (Deci & Ryan, 1985), Social Cognitive Theory (Bandura, 1986), and Krashen’s Input Hypothesis (1985), the study investigated the combined influence of learner-related and school-related factors on literacy outcomes. Specifically, it explored reading motivation, study habits, language exposure, teaching strategies, availability of reading materials, and classroom learning environment. The study employed a quantitative descriptive–correlational research design. Data were gathered from 30 purposively selected struggling Grade 7 and Grade 8 students using a researcher-made structured questionnaire validated through expert review. Descriptive statistics, including frequency, percentage, and weighted mean, were used to describe respondent characteristics and determinant levels, while Pearson Product–Moment Correlation Coefficient determined relationships among variables at the 0.05 significance level. Findings revealed high levels of reading motivation and positive study habits among respondents, while language exposure was moderate. Instructional practices and classroom learning conditions generally supported vocabulary development, although access to reading materials remained limited. Statistical analysis showed a significant moderate positive relationship (r = 0.58) between the identified determinants and English reading comprehension and vocabulary performance. Among the determinants, reading motivation emerged as the strongest predictor of literacy outcomes. The study concluded that learner engagement, effective study behaviors, and increased language exposure collectively contribute to improved reading comprehension and vocabulary performance. It recommended differentiated reading activities, expanded language exposure opportunities, improved access to reading resources, and sustained learner-centered instructional practices to strengthen literacy development. This study aligns with Sustainable Development Goal (SDG) 4: Quality Education by supporting equitable literacy development and strengthening foundational learning outcomes. It also relates to SDG 10: Reduced Inequalities through efforts to address literacy disparities among struggling learners. The sustainability impact of the study lies in supporting educational and institutional sustainability through evidence-based literacy interventions, improved instructional planning, and strengthened school practices that promote long-term learner development.